2019
DOI: 10.21608/jpp.2019.59469
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Applications of Nano Chitosan-Urea and Inoculation with Mycorrhiza on Kohlrabi (Brassica oleracea Var. Gongylodes, L.)

Abstract: The current research aims at producing high kohlrabi knob yield with better quality traits using nanochitosan-urea (versus urea) as a foliar spray in presence of mycorrhiza (AMF) as plant inoculants either solely or in combinations with each other. This investigation was carried out under the field conditions for two successive seasons (2015/2016 and 2016/2017). In this concern, microrrhizal inoculations were set up in the main plots whereas the foliar application of nano-urea was arranged in the sub-plots, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…Close examination of the present data, nitrogen, phosphorus and potassium concentrations in plant tissue were remarkable potent in mycorrhizal plants than that of nonmycorrhizal plants either in the presence or without the pathogen [ 30 ]. Whereas, the presence of Chitosan NPs in AM plants leads to increasing nutrient content of plants by about 40% and 47% for nitrogen and 52% and 65% for phosphorus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Close examination of the present data, nitrogen, phosphorus and potassium concentrations in plant tissue were remarkable potent in mycorrhizal plants than that of nonmycorrhizal plants either in the presence or without the pathogen [ 30 ]. Whereas, the presence of Chitosan NPs in AM plants leads to increasing nutrient content of plants by about 40% and 47% for nitrogen and 52% and 65% for phosphorus.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the best application techniques for certain crops and diseases, extensive research and field tests are required. The novel theoretic has been elevated that chitosan NPs can favorable influence on crop and soil microbial societies as AMF [ 30 ]. El Amerany et al [ 31 ] reported that combined chitosan with AMF increase the stem cortex of tomato strains and improved sugar and protein content more than the non-inoculated one.…”
Section: Introductionmentioning
confidence: 99%
“…managements, observed that the chemical composition of applied farmyard manure had considerable amounts of macronutrients and small amounts of micronutrients [39,56]; they discovered that nutrients like nitrate, calcium, magnesium, and other elements were being lost from crop root zones to subhorizons, where they could be absorbed by species with deep roots and returned to the surface through litter. Te diference in exchangeable calcium between cultivated land and a backyard garden was likely due to signifcant acidifcation processes brought on by the removal of basic cations (Na, Ca, Mg, and K) by crop uptake, leaching, and erosion.…”
Section: Exchangeable Basic Cationsmentioning
confidence: 99%
“…Application of nanobiofertilizers on wheat plants enhances the spike length, spike number, grain yield, and weight by reducing the duration of physiological maturity (Mardalipour et al, 2014). Spraying Brassica oleracea plants with CS-urea NPs (1,000 mg/L) and plant mycorrhiza cut off the input of chemical nitrogen fertilizers by 33.3%; this is recorded as a comparable application for the full dose of urea (Shams, 2019). Although lack of fundamental knowledge on the interactions between NPs and plant hinders the efficient development and implementation of these formulations (Kalia and Kaur, 2019) currently, NFs proved to increase the growth and plant components of harvests by expanding the growing phase (Mardalipour et al, 2014).…”
Section: Micronutrient Nanofertilizersmentioning
confidence: 99%
“…Most of the studies have focused on utilizing iron-based NMs for soil remediation strategies (Baragaño et al, 2020a;Fajardo et al, 2020;Gil-Díaz et al, 2016, 2019.…”
Section: Iron-based Npsmentioning
confidence: 99%